Níveis de nigrogênio no cultivo de híbridos de sorgo versus milho na 2ª safra de verão para silagem e grãos - Guimaraes, Larissa Juliane (2022)
Higher production costs and risks due to new bugs (Daubulus maydis), associated with frost and water deficit has motivated farmers to find new option to the corn grown, within sorghum appears as a good option. New sorghum hybrids are far more productive, although, it’s response to nitrogen levels still need to be validated by the research aiming to help decision making. Moreover, due to it’s good adaptance, sorghum silage can be costly effectively when compared to corn. To evaluate these hypotheses, experiments were carried out at the 2020/2021 and 2021/22 2nd summer growing season on the UTFPR campus in Dois Vizinhos, Paraná. At the 1st year, were established an experiment in a 4 x 4 factorial scheme where factor A refers to 4 sorghum hybrids (S15IO033, B10I002F-X800, 1G100 and 1G233) and factor B to 4 nitrogen levels (0,40, 80 and 120 kg N ha-1) applied in topdress, single dose using urea as a source. On the 2nd year, three hybrids of sorghum SS318, 1G100 and 1G233 and one of corn (P3310), with four levels of N (0, 40, 80 and 120 kg N ha-1) in a 3+1 x 4 factorial scheme were evaluated, being both experiments set up in a randomized block design with three repetitions. At 2019/20, the hybrid code B10I002f-x800 presented the highest biomass yield in relation to the others. Regarding to the N response, this material showed quadratic nitrogen levels response, showing an increase of 31.9 kg of DM per kg of applied N. The hybrid S15L033 and 1G10 had a higher mass of one thousand grains compared to the others in the 2019/20 harvest. Regarding grain yield, the hybrid S15L033 produced 1,138 kg ha-1 more than the least productive material. Comparing grain yield between sorghum materials versus corn, in the 2020/2 harvest, corn was more productive than all the sorghum hybrids at different doses. The smallest and largest difference was of 1,469 and 3,803 kg ha-1 between the corn hybrid and sorghum S1510033 with 80 kg of N kg ha-1 and 1G233 with 0 kg of N kg ha-1. For dry mass yield in the 2020/21 season, the sorghum hybrid S318 did not differ from the corn hybrid when 40, 80 and 120 kg N ha-1 were used. The other hybrids showed lower dry matter yield. Regarding bromatological quality, there was no difference among sorghum hybrids and corn hybrid for the NDF and ADF content, with the exception to the 1G100 and SS318 at the treatment without nitrogen, which present lower results. For the crude protein content, several sorghum hybrids showed similar levels of those presented by corn, although, some of them showed lower values. There are specific sorghum hybrid for grain or silage. Corn remain the first option when grown for grains, although, sorghum showed to be as good as corn when used for silage.